Fluid Attention in Education: Conceptual and Neurobiological Framework - Bruya, Brian; Tang, Yi-Yuan (Frontiers in Psychology, 2021)
Attention is indispensable to our learning, performance, relationships, health, and daily life, and yet laboratory studies of attention have only scratched the surface of these lived varieties of attention. In this article, we begin with William James' theory of derived involuntary attention, which has largely been ignored in laboratory research. We then show that there is a gap in our attention vocabulary and the theory that underpins it, which depend on an incomplete voluntary/involuntary dichotomy. The negative effects of this dichotomy stretch beyond laboratory research to clinical diagnosis, influencing how we understand so-called attention deficits. To fill the gap between voluntary and involuntary, we introduce a third kind of attention--fluid attention (also called postvoluntary attention), which is goal-directed and selective, like voluntary attention, but also effortless and drawn to its source, like involuntary attention. Fluid attention is a rediscovery of James' derived involuntary attention. A distinguishing feature of fluid attention is its motivational component, which, we show, neurophysiologically also reveals a gap in the neurocognitive literature on attention. Recognizing fluid attention as fundamentally motivational allows ADHD to be redefined as a motivational rather than an attentional deficit, which we go on to show has significant implications for both special and regular education.